Cobalamins and cobalamin-dependent enzymes in Candida utilis. - Poston, J M (1979)
Candida utilis has been shown to contain 4.7 pmol of cobalamin per g of wet cell paste. Purification of the cobalamin showed it to be a mixture of methylcobalamin and adenosylcobalamin. Two cobalamin-dependent enzyme systems have been found in the yeast: methylcobalamin-dependent methionine biosynthesis and leucine 2,3-aminomutase. The cobalamin extracted from the yeast is as effective as authentic adenosylcobalamin in stimulating leucine 2,3-aminomutase.